Pengembangan e-LKPD Berbasis SQ4R Menggunakan Liveworksheets pada Materi Senyawa Hidrokarbon - Aisyah; Susilawati, Susilawati; Linda, Roza (Chemistry Education Practice, 2023)
This study aims to develop Electronic Student Worksheets Based on SQ4R using Liveworksheets on Hydrocarbon Compounds material, which is valid based on aspects of content feasibility, SQ4R characteristics, language, presentation, display, software utilization and knowing user responses to E-LKPD. The type of this research is research and development (R and D) with reference to the 4D development process. The subject of this research is a student worksheet based on SQ4R. The data collection instrument is the validation given to four validators, and from the analysis of the data obtained the validity of the aspects of the feasibility of content, SQ4R characteristics, language, presentation, display, software utilization is 96.42%; 97.91% ; 97.5% ; 95.83% ; 93.05% ; 96.42%, with valid category. The e-LKPD which was validated by the validator was tested on one teacher, getting the response results with a percentage of 93.99% with very good criteria. Based on the results of data analysis, it can be concluded that the SQ4R-based E-LKPD produced is valid and can be used for hydrocarbon compounds material.